6(X+5)-(4x-4)=

Simple and best practice solution for 6(X+5)-(4x-4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(X+5)-(4x-4)= equation:


Simplifying
6(X + 5) + -1(4x + -4) = 0

Reorder the terms:
6(5 + X) + -1(4x + -4) = 0
(5 * 6 + X * 6) + -1(4x + -4) = 0
(30 + 6X) + -1(4x + -4) = 0

Reorder the terms:
30 + 6X + -1(-4 + 4x) = 0
30 + 6X + (-4 * -1 + 4x * -1) = 0
30 + 6X + (4 + -4x) = 0

Reorder the terms:
30 + 4 + 6X + -4x = 0

Combine like terms: 30 + 4 = 34
34 + 6X + -4x = 0

Solving
34 + 6X + -4x = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-34' to each side of the equation.
34 + 6X + -34 + -4x = 0 + -34

Reorder the terms:
34 + -34 + 6X + -4x = 0 + -34

Combine like terms: 34 + -34 = 0
0 + 6X + -4x = 0 + -34
6X + -4x = 0 + -34

Combine like terms: 0 + -34 = -34
6X + -4x = -34

Add '4x' to each side of the equation.
6X + -4x + 4x = -34 + 4x

Combine like terms: -4x + 4x = 0
6X + 0 = -34 + 4x
6X = -34 + 4x

Divide each side by '6'.
X = -5.666666667 + 0.6666666667x

Simplifying
X = -5.666666667 + 0.6666666667x

See similar equations:

| 2(3p-1)-3(p-4)= | | 78200/(68*46)= | | 6p+10q=400 | | logx^2-1=0 | | (5x^5y^7)^-2/10x^3y^5 | | 56ab/a=0 | | .07(18000-x)+.1x=1590 | | M^4+4m^2-12=0 | | 2a+6b=100 | | 3x-18/9-x= | | 9=3x^2-3x | | sin(2x)+3cos(2x)=0 | | f(-1)=3/(x^5) | | 3x+104=0 | | 5x-4p=27 | | 4x+22=-17+7x | | X-3-5=3 | | 2c+14=6-5 | | 1/5w-3=6/5w | | (9x-y)=0 | | 4x+28=340 | | p+(-2)=6 | | (-3)-3= | | 3x+y=2480 | | v/3=2 | | 5w+5=w-10 | | -116=4x+2(-6x-10) | | 4x-2=-5x+18-2x | | -11x-82=-148 | | 4x-5(-x-2)=9 | | 3=5x+2(-4x-12) | | 382839492818-919383647447= |

Equations solver categories